An exploratory study on the open access policy of selected academic institutions a case study - Mercado, Nathaniel Jhon S.; Dorado, Dan Anthony D. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2016)
Open access is becoming a clear trend even in developing countries. There are some Philippine academic institutions which are part of the ASEAN University Network (AUN) which are now venturing into Open Access particularly in the green road of OA self-archiving. These are the University of the Philippines Diliman Main Library, Ateneo de Manila University Rizal Library, and De La Salle University Taft Library. This study thus assessed the status of these Open Access initiatives of AUN members in the Philippines and come up with a guiding framework in creating Open Access policies for Philippine academic libraries.
This examined the status of Open Access initiatives of each institution with the help of a framework for OA policies. Directors of each library were interviewed because they are the ones heading the initiative for Open Access within their respective institutions. Each case study was presented using the format of the framework presented in this paper to give a clearer context of the status of OA initiatives and policies, and how they could thrive using the framework. The basis of such framework lies in the UNESCO Policy Guidelines for the Development and Promotion of Open Access by Alma Swan.
Upon assessment each institution are currently focused on the green road of OA self-archiving. In assessing their OA initiatives for creating policies, each institution is suggested to make their OA policies mandatory so as to achieve a more effective Open Access output compared to voluntary as evidenced by foreign studies and trends on OA mandates and policies. The scope varies among each institution primarily because of their diverse collections and inclusion of most of their institutional records, however, a common collection which will be made OA are theses and dissertations created by their students and faculty. Funding relies on the budget and support given to them by their parent institution and the policy initiatives are backed by research administrations in each institution. There are no fees charged to authors since they will publish it via the OA repositories of the institution, however, they have the option to venture out to other publication means provided that they comply with the mandates of their institution. With regard to copyright and licensing, each institution is still having some conflicts with their institutional Intellectual Property policies. The authors' works will be deposited to each institutional repository upon publication giving the institution full metadata of the works so as to be archived, but also gives authors options for embargoes to explore other publication means.
The researcher also presented guidelines and samples of Open Access policies based on the framework used in this study. Because this study is exploratory in nature, it is by no means suggesting of a one-stop solutions for Open Access for these institutions or for other similar institutions, but only provides a framework which can be used to develop Open Access policies applicable to the current Philippine setup of scholarly communication.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Open Access Publishing -- Philippines; Academic libraries -- Philippines -- Manila; Academic libraries -- Philippines -- Quezon City